Diagnostic Accuracy of Magnetic Resonance Imaging (MRI) in Diagnosing Anterior Cruciate Ligament Tear (ACL) Taking Arthroscopy as Gold Standard - Tanveer, Namra; Mirza, Tariq Mahmud; Faiz, Ayesha; Shakeel, Fatima; Asad, Maheen (Indus Journal of Bioscience Research, 2025)
Background: Anterior cruciate ligament tear is a frequent cause of post traumatic knee instability. Arthroscopy is the reference standard but is invasive, whereas magnetic resonance imaging is widely used as a noninvasive alternative. Aim: To determine the diagnostic accuracy of magnetic resonance imaging in diagnosing anterior cruciate ligament tear, using arthroscopy as the gold standard. Materials and Methods: A cross sectional survey was conducted in the Department of Diagnostic Radiology, Combined Military Hospital Lahore, over six months (October 2024 to March 2025). Non probability consecutive sampling enrolled 142 patients aged 16 to 55 years with recent knee trauma within two months and positive anterior drawer and Lachman tests. Magnetic resonance imaging was performed on a 0.5 tesla system using multiplanar T1 weighted, T2 weighted, proton density fat saturated, and short tau inversion recovery sequences. Anterior cruciate ligament tear on magnetic resonance imaging was defined as non visualization or disruption with multi fragmented appearance. Arthroscopy was performed under general anaesthesia by a blinded surgical team and tear was defined as disruption of one third or more ligament fibers. A 2 by 2 table was used to compute sensitivity, specificity, predictive values, and diagnostic accuracy. Results: Mean age was 29.4 ± 8.7 years and mean body mass index was 25.6 ± 3.9 kg/m²; 98 (69.0%) participants were male. Right knee involvement was seen in 80 (56.3%). Sports injuries accounted for 65 (45.8%) cases. Arthroscopy confirmed tears in 89 (62.7%). Magnetic resonance imaging yielded 82 true positives, 46 true negatives, 7 false positives, and 7 false negatives, giving sensitivity 92.1%, specificity 86.8%, PPV 92.1%, NPV 86.8%, and accuracy 90.1%. Conclusion: Magnetic resonance imaging showed high diagnostic accuracy for anterior cruciate ligament tear compared with arthroscopy in clinically suspected injuries.